Pola Makan Anak Prasekolah Di TK Gayaman Mojoanyar Mojokerto - Eka Diah Kartiningrum (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2020)
A diet is a way or effort in setting the amount and type of food with a specific purpose such as maintaining the health, nutritional status, prevent or help cure the disease. The purpose of this study was to determine the Diet of Preschool Children at Kindergarten Gayaman Mojoanyar Mojokerto. This type of research used in this research is descriptive. The variables in this study were the children's diet in Kindergarten Gayaman. The population is children in Gayaman Kindergarten in 2014 (25% of the total population. The results of the study on the Diet of Preschool Children explained that more than 50% of the respondents chose to eat 2x1 per day (60%), breakfast from 06-07, 65% respondents choose a regular diet for 4 days> 3 hours, and 30% of respondents often consume fried chicken.The frequency of eating patterns for preschool children is not proportional to the daily calorie needs because adolescents with dense activities really need calories to increase energy. Children really determine the calorie needs in the body Preschool children At Kindergarten Gayaman have a habit of distance between their last eating pattern and sleep> 3 hours, after eating and then sleeping there can be disturbances in the digestive tract. Children can also experience fat accumulation if not accompanied by exercise when finished eating, the diet of preschool children should be done regularly because adolescents are not regular on their diet They tend to experience various comorbidities such as stomach disorders, headaches. And because of that, families should improve the diet of adolescents so they can meet more daily calories